A arte da cura: benzimentos e benzedeiros(as) - Garbo, Magda Guerato (2022)
The objective of this study was to investigate changes in the construction of the role of a healer: past and present and, specifically, to investigate the importance of intergenerationality in a healer's development and the process of benzimento (casting spells) in its various performed modalities. This study is focused on the theoretical assumptions from the Systems Theory, also covering the intergenerationally transmitted family knowledge, Integrative and Complementary Practices (PICs), the benzimento and healer's interaction with Religion, Religiosity and/or Spirituality, and current research on benzimentos and intergenerationality. It consists of some qualitative research, established on multiple case studies, which encompassed 12 interviews: 6 with healers and 6 with blessed people. From collected data, the participants' Family Timeline was built. From interviews analyses, 3 categories have arisen: 1-The construction of the healer's role, highlighting the motivation, the act of being and the practice of healing; 2-The role of intergenerationality in the healer's development; 3-Benzimento processes, individualization, and freedom of practices. A change has also been determined in healers' profiles when compared to those in the past, when practices were orally transmitted. The main change refers to their modus operandi, currently in a virtual environment, considering the COVID-19 pandemic. The search for legitimization in the practice has also been evinced, given the multiplication of formation courses, complementing intergenerationally transmitted knowledge. Healers claim having received a gift granted by some divine entity, report that benzimento is not connected to any specific religion, they carry with themselves legacies and intergenerational missions. Benzimento should not be charged and, therefore, is voluntary and currently practiced in some Brazilian Basic Health Units (UBS)